La gestión de la información científica para fortalecer las competencias investigativas de los docentes de bachillerato general unificado en la unidad educativa Caluma del cantón Caluma. - Arias Pacheco, Zoila Marisela (2015)
This project gives to learn about the management of scientific information and how this can enhance the skills research of teachers of general unified baccalaureate of caluma educational unit, since it offers a continuum of education and training that meets the need of each teacher, already today in day with great waves of information on the internet the individual has accustomed to simply enter a search engine and write it requiring no awareness that, precisely because of the heavy-load of information that exists in the network not all can be considered it as scientific is there where this approach is intended to generate culture and awareness of management of scientific information refers. Previously raised with only know teachers can get it where and how search quality and adequate information in a timely manner satisfying and strengthening their knowledge in a reflective way. Although all with greater emphasis and professional teachers have the urgent need in true training present as a solution to the problem an educational guide that teachers in managing scientific information and at the same time strengthen its powers research, promoting not only personally but for the benefit of the institution and their trainees.